The Fraction Nonconforming m-of-m Control Chart with Warning Limits - Kuber Khilare, Shashikant; Tukaram Shirke, Digambar (Thailand Statistician, 2023)
This article addresses the development of the fraction nonconforming m-of-m control chart with warning limits to increase the sensitivity of the fraction nonconforming control chart. When the process runs in an in-control state for a long time, it is appropriate to investigate the steady-state average run length. We use average run length, standard deviation of run length and quartiles to measure the performance of the proposed chart under steady-state mode. The Markov chain technique is employed to compute the average run length and standard deviation of run length. The study shows that the proposed runs rule schemes with warning limits performs better than the runs rule schemes without warning limits to detect small to moderate shifts. Usefulness of the proposed control chart is explained by giving the numerical example.